Physical Fitness and Somatic Characteristics of the Only Child - Rodrigues, Luis P.; Lima, Ricardo Franco; Silva, Ana Filipa; Clemente, Filipe Manuel; Camões, Miguel; Nikolaidis, Pantelis Theodoros; Rosemann, Thomas; Knechtle, Beat (Frontiers in Pediatrics, 2020)
The purpose of this study was to examine if only child show differences on somatic growth and physical fitness compared to be a child with siblings. The participants included 542 children (boys: N=270; girls: N=270) between seven and fifteen years of age. Somatic growth (height, weight, body mass index) and physical fitness (handgrip strength; flexed harm hang; 60-sec sit-ups; standing long jump; 10-m shuttle run and PACER test) were assessed. Variance analysis revealed significant advantages for children with siblings in the flexed arm hang (p=0.046), 60-sec sit-ups (p=0.002), 10-m shuttle run (p=0.013) and PACER (p=0.032). An examination of the possible differential effect of sex on the results revealed no significance for physical fitness variables, but significant interaction were found for weight (p=0.004) and body mass index (p=0.005). Despite a lack of interactions between offspring and sex in physical fitness, significant differences between sexes were found in all fitness variables. In conclusion, having siblings showed to be advantageous for general physical fitness in children. This evidence may be used for future analysis and interventions in motor competence, namely considering the growing number of only children in some regions of the world.